Top 100 most-cited articles on apoptosis of non-small cell lung cancer over the past two decades: a bibliometrics analysis - Ma, Leshi; Zhang, Jing; Dai, Zi; Liao, Pei; Guan, Jieshan; Luo, Zhijie (Frontiers in Immunology, 2025)
BackgroundRecently there has been an increasing number of studies have explored apoptosis mechanisms in lung cancer (LC). However, no researchers have conducted a bibliometric analysis of the most cited articles in this field.ObjectiveTo examine the top 100 most influential and cited publications on apoptosis in non-small cell lung cancer (NSCLC) from 2004 to 2023, summarizing research trends and key focus areas.MethodsThis study utilized the Web of Science Core Database (WOSCC) to research NSCLC apoptosis from 2004 to 2023, using keyword selection and manual screening for article searches. Bibliometrix package of R software 4.3.1 was used to generate distribution statistics for the top ten institutions, journals and authors. Citespace6.2. R6 was used to create the visualization maps for keyword co-occurrence and clustering. VOSviewer1.6.19 was used to conduct cluster analysis of publishing countries (regions), with data exported to SCImago Graphica for geographic visualization and cooperation analysis. VOSviewer1.6.19 was used to produced co-citation maps of institutions, journals, authors, and references.ResultsFrom 2004 to 2023, 13316 articles were retrieved, and the top 100 most cited were chosen. These were authored by 934 individuals from 269 institutions across 18 countries and appeared in 45 journals. Citations ranged from 150 to 1,389, with a median of 209.5. The most influential articles appeared in 2005 and 2007 (n=13). The leading countries (regions), institutions, journals and authors were identified as the United States (n=60), Harvard University (n=64), CANCER RESEARCH (n=15), SUN M and YANG JS (n=6). The top five keywords were “expression”, “activation”, “apoptosis”, “pathway” and “gefitinib”. This study indicates that enhancing apoptosis through circular RNA regulation and targeting the Nrf2 signaling pathway could become a key research focus in recent years.ConclusionApoptosis has been the subject of extensive research over many years, particularly in relation to its role in the pathogenesis, diagnosis, and treatment of NSCLC. This study aims to identify highly influential articles and forecast emerging research trends, thereby offering insights into novel therapeutic targets and strategies to overcome drug resistance. The findings are intended to serve as a valuable reference for scholars engaged in this field of study.